Method for producing anhydrous sodium borohydride and anhydrous sodium borohydride
Patent Information
- Application Number
- JP2025062717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0016】 第1から第3の態様によれば、簡単な工程により多角形の晶癖を有し、多角形の頂点の数が5つ以上である水素化ホウ素ナトリウム無水和物を提供できる。
Smart Images

Figure 2026169054000002 
Figure 2026169054000003 
Figure 2026169054000004
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing anhydrous sodium borohydride and anhydrous sodium borohydride.
Background Art
[0002] As hydrogen fuel attracts attention as an alternative energy to fossil fuels, sodium borohydride (SBH) is a promising hydrogen carrier for hydrogen storage, transportation, and as a hydrogen generation source. In consideration of storage methods and the environment, the need for anhydrous sodium borohydride is considered to increase for the purpose of realizing a wider range of usage methods.
[0003] As a conventional production method for sodium borohydride dihydrate, which is a hydrate of anhydrous sodium borohydride, for example, Non-Patent Document 1 discloses a method in which anhydrous sodium borohydride is dissolved in an aqueous sodium hydroxide solution, the solution is stirred at a temperature of 35 to 36°C, filtered under a nitrogen flow, placed in a sealed container, stored in a refrigerator at 0°C for 24 hours, the precipitated crystals are separated from other liquids by filtration, pressed well between filter papers, and lightly dried in vacuum.
Prior Art Documents
Non-Patent Documents
[0004]
Non-Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] However, the proposal in Patent Document 1 had the problem that the process of storing the sodium hydroxide aqueous solution, which is obtained by dissolving anhydrous sodium borohydride, at low temperatures required specialized equipment and time.
[0006] The present invention aims to provide anhydrous sodium borohydride, which can be produced by a simple process. [Means for solving the problem]
[0007] The first embodiment of the method for producing anhydrous sodium borohydride is a method for producing anhydrous sodium borohydride in which the crystal habit includes a polygon, and the number of vertices of the polygon is 5 or more, and includes the steps of: preparing a raw material solution containing water, sodium hydroxide and sodium borohydride at a temperature of 40°C or higher; cooling the raw material solution to a temperature of 8°C or higher and 12°C or lower at a cooling rate of 0.1°C / min or higher and 7°C / min or lower; filtering the cooled raw material solution to obtain a precipitate; and drying the precipitate with dry air, wherein the ratio of the mass of sodium hydroxide to the mass sum of the water and sodium hydroxide in the raw material solution before cooling is 0.5% by mass or higher.
[0008] A second embodiment of a method for producing anhydrous sodium borohydride is a method for producing anhydrous sodium borohydride in which the crystal habit includes a polygon, and the number of vertices of the polygon is 5 or more, and includes the steps of: preparing a raw material solution containing water, sodium hydroxide, and sodium borohydride at a temperature of 40°C or higher; cooling the raw material solution to a temperature of 8°C or higher and 12°C or lower at a cooling rate of 0.1°C / min or higher and 7°C / min or lower; filtering the cooled raw material solution to remove precipitates; and drying the precipitates with dry air, wherein in the raw material solution before cooling, the ratio of the mass of sodium hydroxide to the mass sum of the water and sodium hydroxide is 0.1% by mass or higher, and in the step of cooling the raw material solution, when the temperature of the raw material solution is 28°C or higher and 32°C or lower, a seed crystal containing sodium borohydride is added.
[0009] In the second embodiment, the amount of seed crystal added may be 0.01% by mass or more relative to the raw material solution.
[0010] In the first or second embodiment, the raw material solution may be prepared by adding sodium borohydride to an aqueous solution containing sodium hydroxide.
[0011] In the first or second embodiment, the concentration of sodium hydroxide in the aqueous solution may be 0.1% by mass or more.
[0012] In the first or second embodiment, the raw material solution prepared in the step of preparing the raw material solution may contain 35% by mass or more and 45% by mass or less of the sodium borohydride.
[0013] The third embodiment of anhydrous sodium borohydride has a crystal habit that includes a polygon, and the number of vertices of the polygon is five or more.
[0014] The anhydrous sodium borohydride of the third embodiment may include a hexagonal crystal habit.
[0015] The anhydrous sodium borohydride of the third embodiment may be porous. [Effects of the Invention]
[0016] According to the first to third embodiments, anhydrous sodium borohydride having a polygonal crystal habit and five or more vertices in the polygon can be provided by a simple process. [Brief explanation of the drawing]
[0017] [Figure 1] Figure 1 is a diagram illustrating a method for determining the particle shape of anhydrous sodium borohydride. [Figure 2] Figure 2 is an image illustrating an example of the crystal habit of a seed crystal of sodium borohydride. [Figure 3]Figure 3 is a diagram showing an SEM observation image of the product according to Test Example 3. [Figure 4] Figure 4 is a diagram showing an SEM observation image of the product according to Test Example 7. [Figure 5] Figure 5 is a diagram showing an SEM observation image of the product according to Test Example 8. [Figure 6] Figure 6 is a diagram showing an SEM observation image of the product according to Test Example 9. [Figure 7] Figure 7 is a diagram showing an SEM observation image of the product according to Test Example 10. [Figure 8] Figure 8 is a diagram showing an SEM observation image of the product according to Test Example 10. [Figure 9] Figure 9 is a diagram showing an XRD result of the product according to Test Example 10. [Figure 10] Figure 10 is a diagram showing the result of a moisture absorption test of the product according to Test Example 10. [Mode for Carrying Out the Invention]
[0018] Hereinafter, embodiments according to the present disclosure will be described with reference to the drawings, but the present disclosure is not limited thereto. The constituent elements of the embodiments described below can be appropriately combined. In addition, some constituent elements may not be used. Further, the constituent elements in the embodiments described below include those that can be easily assumed by those skilled in the art, those that are substantially the same, and those within the so-called equivalent range.
[0019] (First Embodiment) The method for producing anhydrous sodium borohydride (NaBH4) according to the first embodiment is a method for producing anhydrous sodium borohydride in which the crystal habit of the crystal includes a polygon, and the number of vertices of the polygon is 5 or more. The method for producing anhydrous sodium borohydride according to the first embodiment includes a step of preparing a raw material solution, a step of cooling the raw material solution, a step of taking out a precipitate, and a step of drying the precipitate.
[0020] (Raw Material Solution Preparation Step) In the process of preparing the raw material solution, a raw material solution containing water, sodium hydroxide (NaOH), and sodium borohydride is prepared. In the first embodiment, the raw material solution is prepared by adding sodium borohydride to an aqueous sodium hydroxide solution and heating it to dissolve the sodium borohydride. The heating method is not particularly limited and can be done by, for example, a water bath.
[0021] In the first embodiment, the step of preparing the raw material solution is carried out at 40°C or higher. This increases the solubility of sodium borohydride in the raw material solution, allowing for more efficient acquisition of anhydrous sodium borohydride. In the first embodiment, it is preferable that the step of preparing the raw material solution is carried out at 50°C or lower. This suppresses the decomposition of sodium borohydride, allowing for more efficient acquisition of anhydrous sodium borohydride.
[0022] In the raw material solution before cooling, the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide is 0.5% by mass or more. In the first embodiment, since the raw material solution is prepared using an aqueous sodium hydroxide solution, the concentration of the aqueous sodium hydroxide solution used in the process of preparing the raw material solution is 0.1% by mass or more. This allows for more efficient acquisition of anhydrous sodium borohydride. In the raw material solution before cooling, the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide is preferably 2% by mass or less, and more preferably 1% by mass or less. This suppresses the adhesion of sodium hydroxide to sodium borohydride and improves the purity of the resulting sodium borohydride.
[0023] The sodium borohydride used in the process of preparing the raw material solution is anhydrous sodium borohydride, but is not limited to this, and may also be hydrated sodium borohydride. The crystal habit of the sodium borohydride used in the process of preparing the raw material solution is not particularly limited, and may be similar to that of a seed crystal containing sodium borohydride, for example, as shown in Figure 2 described later.
[0024] The raw material solution prepared in the raw material solution preparation step preferably contains 35% to 45% by mass of sodium borohydride. This allows for more efficient acquisition of anhydrous sodium borohydride.
[0025] In the process of preparing the raw material solution, it is preferable to stir the raw material solution. The method of stirring the raw material solution is not particularly limited; for example, the raw material solution may be stirred by rotating a stirring rod with blades inside the raw material solution. In this case, the rotation speed of the stirring rod with blades can be set to, for example, 100 rpm or more and 400 rpm or less.
[0026] In the process of preparing the raw material solution, it is preferable to remove any solid phase that could not be dissolved by stirring by filtering the raw material solution after stirring. The method for removing the solid phase from the raw material solution is not particularly limited and can be performed, for example, by vacuum filtration.
[0027] The solid phase is removed at a temperature of 40°C or higher. This increases the solubility of sodium borohydride in the raw material solution, allowing for more efficient acquisition of anhydrous sodium borohydride in the raw material solution cooling step described later.
[0028] (Raw material solution cooling process) In the step of cooling the raw material solution, the raw material solution is cooled to precipitate crystals containing sodium borohydride. The method of cooling the raw material solution is not particularly limited and may be water-cooled or air-cooled.
[0029] The cooling rate of the raw material solution is 0.1°C / min or more and 7°C / min or less. Preferably, the cooling rate of the raw material solution is 0.1°C / min or more and 1°C / min or less. In this disclosure, the cooling rate refers to the value obtained by dividing the temperature difference from the cooling start temperature to the cooling end temperature by the time required for cooling. When the cooling rate of the raw material solution satisfies the above lower limit, supercooling of the raw material solution can be suppressed and crystal precipitation can be promoted. When the cooling rate of the raw material solution satisfies the above upper limit, crystal growth is promoted.
[0030] The temperature at which the cooling of the raw material solution is terminated (cooling termination temperature) is preferably between 8°C and 12°C. This allows for a simpler cooling system.
[0031] After the cooling of the raw material solution is complete, it is preferable to leave the raw material solution standing at the cooling completion temperature for at least one hour. This allows for an increase in the amount of precipitate.
[0032] (Precipitate removal process) In the process of extracting precipitates, the precipitates are recovered from the cooled raw material solution. More specifically, the recovery of the precipitates is carried out, for example, by centrifugal filtration.
[0033] (drying process) In the process of drying the precipitate, the extracted precipitate is dried in dry air. This removes moisture adhering to the surface of the precipitate and water of hydration contained in the precipitate. In this disclosure, dry air refers to air with a humidity of 20% or less. The drying temperature of the precipitate is preferably 35°C or lower. The drying of the precipitate is preferably carried out for 15 hours or more, and more preferably for 24 hours or more.
[0034] Based on the above, a product of anhydrous sodium borohydride is obtained in which the crystal habit of this disclosure includes polygons and the number of vertices of the polygons is five or more. Here, whether or not the precipitate is anhydrous sodium borohydride can be determined by XRD (X-ray Diffraction). Specifically, if the precipitate is measured with powder XRD and the obtained diffraction peak is attributed to anhydrous sodium borohydride, then the precipitate can be determined to be anhydrous sodium borohydride. The method for determining whether or not the precipitate includes a polygonal crystal habit with five or more vertices will be described later in the description of anhydrous sodium borohydride in this disclosure.
[0035] (Second Embodiment) The second embodiment differs from the first embodiment in that a seed crystal containing sodium borohydride is added during the step of cooling the raw material solution. The anhydrous sodium borohydride according to the second embodiment will be described below, but the same points as in the first embodiment will not be explained.
[0036] In the step of cooling the raw material solution according to the second embodiment, a seed crystal containing sodium borohydride is added.
[0037] Figure 2 is an image showing an example of the crystal habit of a sodium borohydride seed crystal. The seed crystal containing sodium borohydride may be, for example, commercially available sodium borohydride powder, sodium borohydride hydrate, or anhydrous sodium borohydride. Furthermore, the crystal habit of the seed crystal is not particularly limited, but from the viewpoint of seed crystal availability, for example, as shown in Figure 2, the crystal habit of the seed crystal is preferably a massive, rectangular, or plate-like shape with a smooth surface.
[0038] The temperature at which the seed crystal is added is preferably between 28°C and 32°C. This ensures that the seed crystal, which will act as a crystal nucleus, is added at the temperature at which the precipitation of sodium borohydride crystals begins, thereby promoting crystal precipitation.
[0039] The amount of seed crystal added is preferably 0.01% by mass or more relative to the raw material solution. This promotes the precipitation of crystals whose crystal habit includes polygons and whose polygons have five or more vertices. The amount of seed crystal added is more preferably 0.5% by mass or less relative to the raw material solution. This makes the production of anhydrous sodium borohydride easier.
[0040] In the second embodiment, the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide in the raw material solution before cooling is 0.1% by mass or more. In the first embodiment, the raw material solution is prepared using an aqueous sodium hydroxide solution, so the concentration of the aqueous sodium hydroxide solution used in the process of preparing the raw material solution is 0.1% by mass or more. This allows for more efficient acquisition of anhydrous sodium borohydride. In particular, in the second embodiment, since a seed crystal containing sodium borohydride is added, supercooling is suppressed and crystal growth with the seed crystal as a nucleus is promoted, even at a low concentration of sodium hydroxide.
[0041] (Third embodiment) Hereinafter, as a third embodiment, the anhydrous sodium borohydride obtained by the method for producing anhydrous sodium borohydride according to the first and second embodiments described above will be explained in detail.
[0042] In the third embodiment, the crystal habit of anhydrous sodium borohydride preferably includes polygons with five or more vertices, i.e., polygons with five or more vertices, and more preferably includes hexagons. This improves water absorption and solubility in water. The crystal habit of anhydrous sodium borohydride can be determined by observing the particles with an electron microscope such as a Scanning Electron Microscope (SEM). More specifically, if at least one particle of anhydrous sodium borohydride containing a polygon with five or more vertices is found in the electron microscope image of anhydrous sodium borohydride, then the crystal habit of anhydrous sodium borohydride can be said to include polygons with five or more vertices. Furthermore, if at least one particle of anhydrous sodium borohydride containing a polygon with six vertices is found in the electron microscope image of anhydrous sodium borohydride, then the crystal habit of anhydrous sodium borohydride can be said to include hexagons. Because the crystal habit of anhydrous sodium borohydride has the shape described above, gaps are more easily formed between the particles of anhydrous sodium borohydride, improving its fluidity and thus making it easier to handle.
[0043] Figure 1 is a diagram illustrating the method for determining the shape of anhydrous sodium borohydride particles. Figure 1 is a portion of the electron microscope image of the particles related to Test Example 3. Below, using the observed image of the anhydrous sodium borohydride particles shown in Figure 1, the method for determining the shape of anhydrous sodium borohydride particles will be explained in detail in three steps, S1 to S3.
[0044] In the first step S1, the observed image of the anhydrous sodium borohydride particle is converted to grayscale using image analysis software, and then a portion of the particle's outline is extracted. Here, the particle's outline refers to the contour of the particle and the lines that appear due to contrast differences within the particle. In the first step S1, a straight line L1 is extracted from the outline of the anhydrous sodium borohydride particle. Here, the portion of the outline that falls within a rectangular region where the length in the longitudinal direction is 250 μm or more and the length in the short direction is 1 / 10 or less of the length in the longitudinal direction can be said to be the straight line L1. In other words, the straight line L1 refers to a portion of the particle's outline that extends 250 μm or more, where the curvature of the outline perpendicular to the direction of extension is within a range of 1 / 10 or less of the extension length.
[0045] As the second step S2, extension lines L2 are drawn from both ends of the line L1 in the direction of extension of the line L1, with the same length as the line L1.
[0046] In the second step S2, if there is a region that satisfies (1) to (3) below, then, as shown in Figure 1, that region becomes the region AR to be evaluated in the third step S3. (1) There is a polygonal region enclosed by a straight line L1 and its extension L2. (2) All sides of the polygon include more than half of the straight line L1. (3) The region in question contains at least a portion of the particles.
[0047] In the second step S2, if there is no region that satisfies (1) to (3) above, select two lines in which one extension intersects another extension or line, and the other extension does not intersect another extension or line, and connect the ends of each of these lines on the other extension side with an imaginary line. If this satisfies (1') to (4') below, the region of the polygon becomes the region AR to be evaluated in the third step S3. (1') There is a polygonal region enclosed by a straight line L1, an extension line L2, and an imaginary line. (2') One of the sides of the polygon is an imaginary line. (3') All non-imaginary sides of the polygon include more than half of the line L1. (4') At least a portion of the particles are contained within the region.
[0048] In the second step S2, if none of the above conditions (1) to (3) and (1') to (4') are met, it is determined that the anhydrous sodium borohydride particles being measured do not contain polygons.
[0049] In the third step S3, as shown in Figure 3, if the shape of region AR is a polygon with five or more vertices extracted in the second step S2, it is determined that the anhydrous sodium borohydride particles to be measured are not square or plate-shaped, but contain polygons with five or more vertices. Also, if the shape of region AR is a polygon with six vertices extracted in the second step S2, it is determined that the anhydrous sodium borohydride particles to be measured contain hexagons.
[0050] The anhydrous sodium borohydride according to the third embodiment is preferably porous. This increases the surface area and improves hygroscopicity. In this disclosure, whether or not it is porous can be determined by observation of an image using an electron microscope such as a scanning electron microscope (SEM).
[0051] (Example test) The following describes the effects of this embodiment in more detail using test examples, but this embodiment is not limited to these examples.
[0052] Table 1 shows the manufacturing conditions and results for sodium borohydride in Test Examples 1 to 10. In the tests, the products for Test Examples 1 to 10 were synthesized using the materials and manufacturing conditions shown in Table 1. Here, "SBH" in Table 1 refers to anhydrous sodium borohydride.
[0053] [Table 1]
[0054] In Table 1, the crystal habit of anhydrous sodium borohydride was evaluated as "A" if the crystal habit of anhydrous sodium borohydride was a polygon with 5 or more vertices, "B" if the crystal habit of anhydrous sodium borohydride included a polygon with 5 or more vertices, and "C" if the crystal habit of anhydrous sodium borohydride did not include a polygon with 5 or more vertices.
[0055] [Test Example 1] Test Example 1 is a comparative example. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the sodium boro hydroxide (SBH) concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 200 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 1.2°C / min. In Test Example 1, no seed crystals were added. After the cooling of the raw material solution was complete, the solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature between 30°C and 35°C and a humidity of 20%. The product related to Test Example 1 was obtained through the above process.
[0056] [Test Example 2] Test Example 2 is a comparative example. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 300 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 0.32°C / min. In Test Example 2, no seed crystals were added. After the cooling of the raw material solution was complete, the solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 2 was obtained through the above steps.
[0057] [Test Example 3] Test Example 3 is a comparative example. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 300 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 0.16°C / min. In Test Example 3, no seed crystals were added. After the cooling of the raw material solution was complete, the solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 3 was obtained through the above steps.
[0058] [Test Example 4] Test Example 4 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 300 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 1.2°C / min. In the step of cooling the raw material solution in Test Example 4, when the temperature of the raw material solution reached 30°C, 0.05% by mass (0.1045 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 4 was obtained by the above steps.
[0059] [Test Example 5] Test Example 5 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 24 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 36 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 150 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 5.8°C / min. In the step of cooling the raw material solution in Test Example 5, when the temperature of the raw material solution reached 30°C, 0.05% by mass (0.031 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product relating to Test Example 5 was obtained by the above steps.
[0060] [Test Example 6] Test Example 6 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 300 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 1.4°C / min. In the step of cooling the raw material solution in Test Example 6, when the temperature of the raw material solution reached 30°C, 0.05% by mass (0.1045 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 6 was obtained by the above steps.
[0061] [Test Example 7] Test Example 7 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 24 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 36 g of a 0.1% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 150 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 6.4°C / min. In the step of cooling the raw material solution in Test Example 7, when the temperature of the raw material solution reached 30°C, 0.10% by mass (0.06 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 7 was obtained by the above steps.
[0062] [Test Example 8] Test Example 8 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 24 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 36 g of a 0.5% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous solution of sodium hydroxide was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 100 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 4.8°C / min. In the step of cooling the raw material solution in Test Example 8, when the temperature of the raw material solution reached 30°C, 0.05% by mass (0.03 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 8 was obtained by the above steps.
[0063] [Test Example 9] Test Example 9 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 24 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 36 g of a 0.5% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous solution of sodium hydroxide was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 100 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 4.2°C / min. In Test Example 9, no seed crystals were added. After the cooling of the raw material solution was complete, the solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product according to Test Example 9 was obtained through the above steps.
[0064] [Test Example 10] Test Example 10 is an example of a real-world application. As shown in Table 1, a raw material solution was prepared by adding 80 g of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to 120 g of a 0.5% by mass aqueous solution of sodium hydroxide (NaOH) so that the SBH concentration in the raw material solution was 40% by mass. In preparing the raw material solution, the aqueous sodium hydroxide solution was heated to 40°C and stirred by rotating a stirring rod with blades at a rotation speed of 200 rpm. The raw material solution was then cooled to 10°C at a cooling rate of 0.125°C / min. In the step of cooling the raw material solution in Test Example 10, when the temperature of the raw material solution reached 30°C, 0.09% by mass (0.18 g) of sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the raw material solution as a seed crystal. After the cooling of the raw material solution was completed, the raw material solution was filtered under reduced pressure to obtain a precipitate as the product. The precipitate was dried for 24 hours in dry air at a temperature of 30°C to 35°C and a humidity of 20%. The product relating to Test Example 10 was obtained by the above steps.
[0065] Figure 3 shows an SEM image of the product related to Test Example 3. As shown in Table 1 and Figure 3, in Test Examples 1 to 3, the crystal habit of anhydrous sodium borohydride was heterogeneous and did not contain polygons with five or more vertices.
[0066] Furthermore, in Test Examples 1 to 3, crystal precipitation did not begin at 30°C during the cooling of the raw material solution. Instead, precipitates rapidly formed when the temperature reached 10°C to 15°C, resulting in a sherbet-like product. This suggests that in Test Examples 1 to 3, the raw material solution was supercooled, preventing the crystal habit of anhydrous sodium borohydride from growing into a shape containing polygons with five or more vertices.
[0067] Figure 4 shows the SEM image of the product from Test Example 7. Figure 5 shows the SEM image of the product from Test Example 8. Figure 6 shows the SEM image of the product from Test Example 9. As shown in Table 1 and Figures 4 to 6, in Test Examples 4 to 9, the crystal habit of anhydrous sodium borohydride included polygons with five or more vertices (region AR). More specifically, in the products from Test Examples 4 to 9, particles with square, plate-like, or massive crystal habits, and particles with crystal habits including hexagons were observed.
[0068] Figures 7 and 8 show SEM images of the product related to Test Example 10. Figure 8 is an enlarged view of region D in Figure 7. As shown in Table 1, Figures 7 and 8, in Test Example 10, the crystal habit of anhydrous sodium borohydride was a polygon with five or more vertices, and the number of vertices of the polygon of the crystal habit became six, resulting in a hexagonal crystal habit of anhydrous sodium borohydride (region AR). Furthermore, as shown in Figure 8, the anhydrous sodium borohydride related to Test Example 10 was porous.
[0069] Figure 9 shows the XRD results of the product related to Test Example 10. In Figure 9, the solid line in the upper graph shows the XRD measurement results of the product related to Test Example 10, and the dotted lines in the upper and lower graphs show the data for anhydrous sodium borohydride (ICDD PDF-2:00-009-0386) in the database. As shown in Figure 9, it was confirmed that the product in Test Example 10 was anhydrous sodium borohydride.
[0070] From the above results, in Test Examples 8 to 10, where the NaOH concentration of the sodium hydroxide aqueous solution was 0.5% by mass or higher, the crystal habit of the product included polygons with 5 or more vertices, whereas in Test Examples 1 to 3, where the NaOH concentration of the sodium hydroxide aqueous solution was less than 0.5%, the crystal habit of the product did not include polygons with 5 or more vertices. This indicates that by setting the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide in the raw material solution before cooling to 0.5% by mass or higher, sodium borohydride containing polygons with 5 or more vertices can be obtained.
[0071] From the above results, in Test Examples 4 to 8 and Test Example 10, where seed crystals were added to a sodium hydroxide aqueous solution with a NaOH concentration of 0.1% by mass or higher, the crystal habit of the product contained polygons with 5 or more vertices, whereas in Test Examples 1 to 3, where no seed crystals were added, the crystal habit of the product did not contain polygons with 5 or more vertices. This indicates that by adding seed crystals to the raw material solution before cooling, where the ratio of sodium hydroxide mass to the mass sum of water and sodium hydroxide is 0.1% by mass or higher, sodium borohydride containing polygons with 5 or more vertices can be obtained.
[0072] (Moisture absorption experiment) Furthermore, a hygroscopic experiment was conducted on the anhydrous sodium borohydride related to Test Example 10. In the moisture absorption experiment, as an example, anhydrous sodium borohydride according to Test Example 10 was left standing in an air environment at a temperature of 25°C and a humidity of 35%, and the increase in mass relative to the mass at the start of the moisture absorption test (mass increase rate) was measured. That is, the mass increase rate (%) was calculated as follows: Mass at measurement - Mass at the start of the test / (Mass at the start of the test) × 100.
[0073] As a comparative example, a hygroscopic experiment was conducted on sodium tetrahydroborate powder (Wako Grade 1, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the same manner as the anhydrous sodium borohydride used in Test Example 10.
[0074] Figure 10 shows the results of a hygroscopic experiment on the product related to Test Example 10. As shown in Figure 10, in the example where the anhydrous sodium borohydride was porous (Test Example 10), the mass increase rate increased faster than in the comparative example, which used commercially available anhydrous SBH powder that was not porous. Therefore, it can be seen that the porous nature of anhydrous sodium borohydride improves its water absorption. [Explanation of symbols]
[0075] L1 straight line L2 extension line AR area
Claims
1. A method for producing anhydrous sodium borohydride, wherein the crystal habit of the crystal includes polygons, and the number of vertices of the polygon is five or more. A step of preparing a raw material solution containing water, sodium hydroxide, and sodium borohydride at a temperature of 40°C or higher, A step of cooling the raw material solution to a temperature of 8°C to 12°C at a cooling rate of 0.1°C / min to 7°C / min, A step of filtering the cooled raw material solution to remove precipitates, The process includes drying the precipitate with dry air, A method for producing anhydrous sodium borohydride, wherein, in the raw material solution before cooling, the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide is 0.5% by mass or more.
2. A method for producing anhydrous sodium borohydride, wherein the crystal habit of the crystal includes polygons, and the number of vertices of the polygon is five or more. A step of preparing a raw material solution containing water, sodium hydroxide, and sodium borohydride at a temperature of 40°C or higher, A step of cooling the raw material solution to a temperature of 8°C to 12°C at a cooling rate of 0.1°C / min to 7°C / min, A step of filtering the cooled raw material solution to remove precipitates, The process includes drying the precipitate with dry air, In the raw material solution before cooling, the ratio of the mass of sodium hydroxide to the mass sum of water and sodium hydroxide is 0.1% by mass or more. A method for producing anhydrous sodium borohydride, comprising the step of cooling the raw material solution, wherein when the temperature of the raw material solution is between 28°C and 32°C, a seed crystal consisting of sodium borohydride dihydrate is added.
3. The method for producing anhydrous sodium borohydride according to claim 2, wherein the amount of seed crystal added is 0.01% by mass or more relative to the raw material solution.
4. A method for producing anhydrous sodium borohydride according to any one of claims 1 to 3, wherein the step of preparing the raw material solution is to add sodium borohydride to an aqueous solution containing sodium hydroxide to prepare the raw material solution.
5. The method for producing anhydrous sodium borohydride according to any one of claims 1 to 3, wherein the raw material solution prepared in the step of preparing the raw material solution contains 35% by mass or more and 45% by mass or less of sodium borohydride.
6. The crystal habit of the crystal includes polygons, Anhydrous sodium borohydride, wherein the number of vertices of the polygon is five or more.
7. The anhydrous sodium borohydride according to claim 6, wherein the crystal habit of the crystals includes a hexagonal shape.
8. An anhydrous sodium borohydride according to claim 6 or 7, wherein the anhydrous sodium borohydride is porous.